GOOD CORPORATE GOVERNANCE PRINCIPLES IN THE MANAGEMENT OF LIMITED LIABILITY COMPANY - henry aspan (International Journal of Law Reconstruction, 2017)
ABSTRACTCorporate governance (corporate governance) is a concept which still debatable among experts in describing it. The purpose of this study is to explore how the implementation and principle problems of good corporate governance in the management of current limited liability company. This research is kind of library research with normative juridical approach, the approach used was the concept of legit positivism which states that the law is identical to written norms established and enacted by authorized bodies or authorities. The result is known that Law Number 40 Year 2007 regarding Limited Liability Company does not explicitly regulate the implementation of Good Corporate Governance principles. The GCG principle setting is explicitly found only in the Regulation of the Minister of State-Owned Enterprises and Bank Indonesia Regulation, so it does not bind the limited liability company in general.